2017
DOI: 10.1089/dia.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Calculator Reduces Hypoglycemia in the Short Term and Fear of Hypoglycemia in the Long Term in Subjects with Type 1 Diabetes (CBMDI Study)

Abstract: Background: In a previous study we demonstrated improvement in metabolic control and reduction in hypoglycemia in people with type 1 diabetes on multiple daily injections, after having used a bolus calculator for 4 months.Objective: To demonstrate whether (1) extending its use (2) or introducing it in the control group, previously subjected to treatment intensification, could further improve metabolic control and related psychological issues.Methods: After the previous clinical trial, in which the subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…Various studies have considered the use of the rapid insulin bolus calculator for patients with DM1, concluding that it contributes to reducing HbA1c levels by an average of 0.91% for poorly controlled patients. In the case of well-controlled patients, although HbA1c levels do not change significantly, there is a decreased risk of post-prandial hypoglycemia, and treatment satisfaction is increased [34,35]. Other systems, such as the synchronisation of the blood glucose sensor and the continuous closed-loop insulin infusion pump, also prevent the risk of hypoglycemia and improve patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have considered the use of the rapid insulin bolus calculator for patients with DM1, concluding that it contributes to reducing HbA1c levels by an average of 0.91% for poorly controlled patients. In the case of well-controlled patients, although HbA1c levels do not change significantly, there is a decreased risk of post-prandial hypoglycemia, and treatment satisfaction is increased [34,35]. Other systems, such as the synchronisation of the blood glucose sensor and the continuous closed-loop insulin infusion pump, also prevent the risk of hypoglycemia and improve patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The Automated Bolus Advisor Control and Usability Study (ABACUS) showed that significantly more patients using the bolus calculator achieved an HbA1c reduction of >0.5% compared to the control group (56% vs 34%; P < 0.01) . A recent study showed a significant increase in the number of patients achieving HbA1c targets and a reduction in hypoglycemia in the bolus calculator use group compared to the active control group . In patients on insulin pump therapy, the rate of bolus calculator use has been correlated with improved glycemic control in both the adult and pediatric populations .…”
Section: Diabetes Apps Automated Decision Support and Bolus Calculamentioning
confidence: 99%
“…271 A recent study showed a significant increase in the number of patients achieving HbA1c targets and a reduction in hypoglycemia in the bolus calculator use group compared to the active control group. 272,273 In patients on insulin pump therapy, the rate of bolus calculator use has been correlated with improved glycemic control in both the adult and pediatric populations. 268,274,275 Overall, these studies show that for MDI and conventional insulin pump patients, use of a bolus calculator reduces burden, improves glycemic control, and improves quality of life.…”
Section: Bolus Calculatorsmentioning
confidence: 99%
“…Few studies found the bolus calculator to be effective in children using CSII. The bolus calculator and CC may have beneficial effects in reducing HbA 1c by improving post-meal glucose, with a higher percentage of values within the target range [ 63 , 64 , 65 ]. Moreover, an insulin pump offers the possibility to tailor insulin delivery to the meal composition through the use of different bolus options: normal, dual wave, or square wave.…”
Section: Insulin-to-carb Ratio (Icr) Insulin Sensitivity Factor (mentioning
confidence: 99%